W-Band Co-Prime Array FMCW MIMO Radar With IPCE Algorithm for High-Angular Resolution - Yu, Taewoo; Kim, Eunbin; Park, Jae-Hyun; Kim, Byung-Sung; Nam, Sangwook (IEEE access, 2023)
In recent years, the research on FMCW radar utilizing the mmWave band has gained significant attention, especially in its application to autonomous driving systems. As a potential replacement for lidar, high-resolution studies have been pursued, necessitating large aperture sizes and a considerable number of channels. In this study, high angular resolution is achieved by creating Multiple-Input Multiple-Output (TDM-MIMO) radar system with 6 Tx 8 Rx based on a co-prime array configuration in the W-band. To simplify the interface between the proposed array configuration and the actual chipsets, a 65-nm CMOS process-based single-channel T/Rx chipset with one-to-one aperture coupling to the antenna is employed, minimizing losses, phase deviations, and radiation pattern impacts seen in direct coupling methods using transmission lines in the mmWave band. In addition, the proposed co-prime array exhibits more sidelobe effects, making it challenging to extract actual targets from the angular spectrum. To tackle this, the paper presents the Iterative Peak Component Elimination (IPCE) algorithm, validated through experiments, effectively resolving the issue. The study's findings contribute to advancing high-resolution radar systems, enhancing target detection and tracking capabilities, particularly in automotive radar applications.